DD-006 Standardisation of antiseptic products distribution in a pharmacy department. (24th March 2015) - Declaye, C; Bary, M; Demazy, B; Hecq, JD
Abstract : Background: Antiseptic products are currently supplied at random over the week. Wards send their orders when their stock is almost used. Purpose: The objectives are a) to standardise the drug chain supply (DCS) of antiseptic products to weekly replenishment by the pharmacy, b) to validate the method of calculating the quantities needed, and c) to set the quantities to have in stock in each ward in collaboration with the nursing team using the LEAN principles. Material and methods: The time taken by the pharmacy to supply antiseptics was recorded per ward for four weeks before standardisation. After calculating the quantities of products required by the "Kanban" calculation method and validation with the nursing team, one ward tested the new method of supply. Finally, time data were again collected for four weeks to compare them with those collected before standardisation. Results: First, the total time spent on supplying antiseptics was 2 h, 31 min and 19 s for all wards included. Before standardisation, we counted 5 prescriptions for the test ward over a 4-week period spread over Wednesday, Thursday and Friday. The total time spent for this ward by the pharmacy was 26 min 37 s. After standardisation and explanations to the nursing and pharmacy teams, we received 4 prescriptions over 4 weeks and spent 12 min 49 s on this activity. Conclusion: This method is suitable for the supply of antiseptics in our institution. The calculation method is appropriate. Moreover, a considerable time saving was observed for the pharmacy and assigned to other activities. It has therefore been decided to standardise the whole institution using this method. References and/or acknowledgements: 1 Mille Y, L'ordonnancement « Total Productive Kanban »: synthèse de 10 années d'expériences vécues. Logistique et Management 1998;6(2):45–60 No conflict of interest.